186 Does Medicaid Cover Male Urethral Sling Surgery? A State-by-State Analysis. Issue 1 (1st April 2022) - Loeb, C.; Barnard, J.; Yafi, F.; Schneider, D.
ABSTRACT: Introduction: Male suburethral slings are one treatment option for stress urinary incontinence (SUI) due to intrinsic sphincter deficiency post-prostatectomy in appropriately selected patients. Some studies report up to 55% social continence, and 23% of respondents reduced use of pads by greater than 50%. Male slings may be preferred in men with limited manual dexterity who have difficulty manipulating an artificial urinary sphincter, or in men with more mild SUI, particularly if there is no history of prior radiation. Existing literature regarding insurance coverage and physician reimbursement overwhelmingly focuses on Medicare and commercial plans, leaving a knowledge gap with respect to the Medicaid population which may contribute to inequitable utilization of this treatment modality for SUI. Objective: To quantify Medicaid coverage for placement and revision of male suburethral slings for correction of male SUI by state. Methods: State Medicaid websites were utilized to access publicly available physician fee schedules. Individual search queries were performed for CPT codes 53440 and 53442, which represent sling operation for correction of male urinary incontinence and removal or revision of sling for male urinary incontinence, respectively. Data were recorded for each device, including the coverage status and physician fees. Results: Medicaid physician fee schedules were accessible for 49 out of 50 US states. All 49 of these states reported coverage for placement of a male urethral sling, and 48 states reported coverage for removal or revision of a male urethral sling. Means and range of physician reimbursement for each procedure were 834.26 (198.00-5, 237.35) for placement of a male urethral sling (53440) and 616.88 (104.27-2, 288.93) for removal or revision of a male urethral sling (53442). Conclusions: Male suburethral sling placement and revision for SUI in the Medicaid population are covered by nearly all states as confirmed by publicly available data. Knowledge of Medicaid coverage for SUI related surgery may result in improvement in the utilization of this treatment option for male SUI and may improve quality of life in the Medicaid cancer survivorship population. Disclosure: No